Neuronal Surface Autoantibodies in Neuropsychiatric Disorders: Are There Implications for Depression? - Zong, Shenghua; Hoffmann, Carolin; Mané-Damas, Marina; Molenaar, Peter; Losen, Mario; Martinez-Martinez, Pilar (Frontiers in Immunology, 2017)
Autoimmune diseases are affecting around 7.6-9.4% of the general population. A number of central nervous system disorders, including encephalitis and severe psychiatric disorders have been demonstrated to associate with specific neuronal surface autoantibodies. It has become clear that specific autoantibodies targeting neuronal surface antigens and ion channels could cause severe mental disturbances. A number of studies have focused or are currently investigating the presence of autoantibodies in specific mental conditions such as schizophrenia and bipolar disorders. However, less is known about other conditions such as depression. Depression is a psychiatric disorder with complex etiology and pathogenesis. The diagnoses criteria of depression are largely based on symptoms but not on the origin of the disease. The question which arises is whether in a subgroup of patients with depression, the symptoms might be caused by autoantibodies targeting membrane associated antigens. Here, we describe how autoantibodies targeting membrane proteins and ion channels cause pathological effects. We discuss the physiology of these antigens and their pathogenicity in relation to depression. Finally, we summarize a number of studies detecting neuronal surface autoantibodies with a special focus on those that the cohorts include depression diagnosis and/ or show depressive symptoms.